Предмет: Алгебра,
автор: ruslan123456789
Упростить выражения.
a) (2a-3b)*(5a+b)-10(a+b)^2
б) (-3x^2y^3)^3*(-2x^5y)^2
P.S. ^-степень
*-умножение
Ответы
Автор ответа:
0
a)=10a^2+2ab-15ab-3b^2-10a^2-20ab-10b^2=-33ab-13b^2
Автор ответа:
0
а)=10а^2+2ab-15ab-3b^2-10a^2-20ab-10b^2=-13b^2-33ab
Автор ответа:
0
-10*(а+b)^2=-10*(a^2+2ab+b^2)=-10a^2-20ab-10b^2
Автор ответа:
0
нет
Автор ответа:
0
ты правильно решила
Автор ответа:
0
извини,перепутала с квадратом разности
Автор ответа:
0
бывает:)
Похожие вопросы
Предмет: Українська мова,
автор: chuprina0807
Предмет: Геометрия,
автор: verbickijroman56
Предмет: Английский язык,
автор: statintevgenii
Предмет: Математика,
автор: vadik2033
Предмет: Алгебра,
автор: mothernet